Reviving the Sultanate of Sulu through its claim over Sabah, 1962-1986 - Norizan Kadir,; Suffian Mansor, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The aftermath of colonialism marked the end of a long-standing and glorious Sultanate of Sulu when it finally lost its power and supremacy under the newly-independent Philippines government. Even after the Philippines finally achieved its independence in 1946, the Sultanate of Sulu again failed to revive its old “kerajaan” as it had been abolished by the Philippines government in 1937. As the sultans and his followers had the historical experience regarding the idea of “kesultanan” and other socio-political concepts, the newly-introduced concept namely the nation-state whereby the idea of the boundary and a new nation was created making the traditional sultanate in desperation to sustain their sovereignty and power. The desperation to re-establish and revive their old glorious “kerajaan” eventually turned into a struggle and rigorous attempts to claim Sabah. Hence, this article aims to illustrate the survival of the Sultanate of Sulu after the death of the last sultan in 1936 and the efforts taken to preserve the sultanate within the modern nation-state system. The method of research used in this study involved library and archival research to obtain primary and secondary sources. Among the primary sources consulted in the study include British records, agreements, correspondence, newspapers, government gazettes, memoranda, speeches, and government official publications. Thus, this article lucidly concludes that various trends and approaches taken by the Sultan of Sulu and his heirs to claim Sabah were a part of their mission to sustain and revive the Sultanate of Sulu.